1995
DOI: 10.1109/61.400956
|View full text |Cite
|
Sign up to set email alerts
|

Case study on the integration of a non-utility induction generator to the Hydro-Quebec distribution network

Abstract: This paper investigates the influence of different factors (such as load and capacitive compensation levels, load and turbine dynamic behaviors, machine parameters) on induction generator self-excitation phenomena and related overvoltages, resulting from a fault andor an unwanted network disconnection. Simulations are performed on a 25 kV distribution network related to an actual project of integration of a nonutility induction generator to the Hydro-Que%ec system. The paper presents the analysis of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…It was concluded that the choice of the DG interface control has an effect on the NDZ and on the choice of the suitable islanding detection method. In [8], the effect of voltage-dependent loads on the operation of an induction generator during an islanding condition was examined. The voltage and frequency deviation were found to be dependent on the load model [8].…”
Section: Performance Of the Ovp/uvp And Ofp/ufp Methods With Voltage Amentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that the choice of the DG interface control has an effect on the NDZ and on the choice of the suitable islanding detection method. In [8], the effect of voltage-dependent loads on the operation of an induction generator during an islanding condition was examined. The voltage and frequency deviation were found to be dependent on the load model [8].…”
Section: Performance Of the Ovp/uvp And Ofp/ufp Methods With Voltage Amentioning
confidence: 99%
“…In [8], the effect of voltage-dependent loads on the operation of an induction generator during an islanding condition was examined. The voltage and frequency deviation were found to be dependent on the load model [8].…”
Section: Performance Of the Ovp/uvp And Ofp/ufp Methods With Voltage Amentioning
confidence: 99%
See 1 more Smart Citation
“…Although most induction generators in operation are employed in wind power plants [3], [6], such machines have also been used in medium-size hydro and thermal plants [3], [7]- [9]. Therefore, in order to keep the results as generic as possible, the mechanical torque was considered constant, i.e., the regulator and prime mover dynamics were neglected.…”
Section: A Induction Generatorsmentioning
confidence: 99%
“…In this context, squirrel-cage rotor induction generators have received augmented attention due to some advantages over synchronous generators such as lower unit cost, smaller size, less maintenance requirement. Although most induction generators in operation are employed in wind power plants [1], [3], these machines have also been used in medium size hydro and thermal plants [1], [4]- [6]. Consequently, it is fundamental to analyze the impacts of the induction generator installation on the distribution network operation as well as to understand the performance of these generators under normal and disturbed operation conditions.…”
Section: Introductionmentioning
confidence: 99%